Visualising Wireless Sensor Networks with NetViewer. (18th June 2012) - Ma, Longhui; Wang, Lei; Shu, Lei; Zhao, Jing; Li, Suran
Visualisation tools make it easier for users to observe the status of the Wireless Sensor Networks (WSNs). So far, developers of WSNs have created various visualisation tools under different project/research backgrounds. These tools, however, are limited in certain application scenarios, since the underlying packet formats are hard coded into the programs. For this purpose, we present NetViewer, a universal visualisation tool for all the applications, and we provide many useful data services to fulfil different needs of various fields.